The effect of bupivacaine on analgesia and safety in patients undergoing hemorrhoidectomy: a meta-analysis - Lu, Haixia; Cai, Min; Zhou, Dongxi; Li, Weiwei; Cao, Hanzhong (Frontiers in Pharmacology, 2024)
Aim: There is no meta-analysis reporting the analgesic effect and safety of bupivacaine in patients undergoing hemorrhoidectomy. This meta-analysis provides quantitative evidence on the effect of bupivacaine in hemorrhoidectomy.Methods: Studies were searched from the Pubmed, Embase, Cochrane Library, and Web of Science. Standardized mean difference (SMD), weighted mean difference (WMD), and odds ratios (OR) with 95% confidence interval (CI) were used as effect indicators. Heterogeneity was assessed using the I 2 index, and sensitivity analysis was conducted to determine the effect of the single study on the pooled results.Results: There were 18 studies included in this meta-analysis. Compared to the other drugs group, pain level at 48h was lower in the bupivacaine combined other drugs group (WMD = -0.65, 95% CI: -1.18 to -0.11, I 2 = 37.50%). Compared to bupivacaine group, the odds of pruritus (OR = 12.11, 95% CI: 1.49 to 98.59, I 2 = 0%) and urinary retention (OR = 4.45, 95% CI: 1.12 to 17.70, I 2 = 0%) were higher and the pain level at 6h (WMD = -2.13, 95% CI: -3.22 to -1.04, I 2 = 64.30%), at 12h (WMD = -1.55, 95% CI: -2.19 to -0.90, I 2 = 56.10%), and at 24h (SMD = -1.15, 95% CI: -1.89 to -0.42, I 2 = 82.5%) were lower in the bupivacaine combined other drugs group.Conclusions: Bupivacaine combined other drugs had a good analgesic effect posthemorrhoidectomy, but the adverse reactions should be considered.